2018
DOI: 10.1371/journal.pone.0208908
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of sputtered gold nanolayers in mass spectrometry imaging for metabolomics applications

Abstract: Mass spectrometry imaging (MSI) is a molecular imaging technique that maps the distribution of molecules in biological tissues with high spatial resolution. The most widely used MSI modality is matrix-assisted laser desorption/ionization (MALDI), mainly due to the large variety of analyte classes amenable for MALDI analysis. However, the organic matrices used in classical MALDI may impact the quality of the molecular images due to limited lateral resolution and strong background noise in the low mass range, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…For MSI (Fig. 2 a), we placed the tissue section onto an ITO-coated glass slide and covered the surface of the tissue with a thin Au nanolayer by sputtering [ 23 ]. For Raman measurements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For MSI (Fig. 2 a), we placed the tissue section onto an ITO-coated glass slide and covered the surface of the tissue with a thin Au nanolayer by sputtering [ 23 ]. For Raman measurements (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The general success, though not broad usage, of these materials on the target plate have led to several different approaches for using alternative inorganic materials for MSI, such as sputtering of metals or the use of metallic NPs, both of which are described in the paragraphs below. Sputtering of metals over tissue sections has produced a number of quality articles that have utilized silver [50], platinum [63], and gold [64]. Sputtering deposits highly pure and homogeneous metal or metal oxide nanolayers onto biological tissue sections.…”
Section: Alternative Matrix Materialsmentioning
confidence: 99%
“…Pt sputtering has been demonstrated on lipids in tissue [68] and in leaves where metabolites of interest were detected, including many with molecular features similar to NTs, such as acetamiprid [63]. Rafols et al showed an Au sputtering MSI experiment that resulted in the potential detection of 25 different compounds, but only 1 of which could be called a small molecule metabolite (i.e., citrulline) [64]. A significant advantage that sputtering demonstrates, compared to organic acid matrices [22], is the lack of analyte delocalization [64].…”
Section: Alternative Matrix Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials or metal layer deposition methods, for instance, dramatically reduce the number of signals related to the LDI promoting material in the low m/z range. Some examples are graphene oxide, silicon or metals such as gold, platinum or silver [ 5 8 ]. Nevertheless, even when these alternatives are used and the number of peaks related to the LDI promoting material is reduced, there is still a need to annotate them in order to reduce spectral complexity and distinguish exogenous from endogenous compounds, especially in untargeted applications.…”
Section: Introductionmentioning
confidence: 99%